INOVASI ECO GREEN CONCRETE DENGAN PEMANFAATAN LIMBAH SAW, LIMBAH BETON, LIMBAH KERAMIK, DAN LIMBAH KARET SEBAGAI SUBSTITUSI AGREGAT - Lilis Tiyani; Amalia; Sukarman; Afrizal Nursin; Muhtarom Riyadi (Universitas Widyatama, 2024)
Eco-green concrete emerged as an environmentally friendly solution using waste or leftover materials from various industries. One of them is the replacement of concrete constituent aggregates with materials that do not damage the environment. In this study, Eco Green Concrete innovation was made with a mixture of Submerged Arc Welding (SAW) which is the residual result of the steel welding process, concrete waste, ceramic waste which is substituted for coarse aggregate and rubber waste which is also substituted for fine aggregate with a percentage of 20% SAW waste, 20% concrete waste, 10% ceramic waste, and 8% rubber waste. The purpose of Eco Green Concrete innovation research is to determine the compressive strength of concrete and is expected to affect the estimation of more economical project costs but the quality of concrete used remains quality and environmentally friendly. The research was conducted experimentally by making concrete test objects that were tested for compressive strength at the age of 7, 14, and 28 days, 28-day split tensile strength test and 28-day bending test. Based on the compressive strength test, the results of the 28-day compressive strength test of concrete without innovation were 34.74 Mpa and 33.92 Mpa of innovation concrete. The results of the split tensile strength test of concrete without innovation amounted to 3.87 Mpa and 3.95 Mpa innovation concrete. The results of testing the flexural strength of concrete without innovation amounted to 4.83 Mpa and concrete innovation amounted to 5.22 Mpa. Keywords : concrete, substitution, waste